2021
DOI: 10.3389/fcosc.2021.796868
|View full text |Cite
|
Sign up to set email alerts
|

Fishers' Ecological Knowledge and Stable Isotope Analysis Reveal Mangrove Estuaries as Key Developmental Habitats for Critically Endangered Sea Turtles

Abstract: Successful conservation of endangered, migratory species requires an understanding of habitat use throughout life stages. When dedicated scientific studies are difficult to conduct, local expert knowledge can provide crucial baseline data to guide study design and aid data interpretation. In 2008, fishers in El Salvador demonstrated that eastern Pacific hawksbill sea turtles (Eretmochelys imbricata)—a population conservation biologists considered virtually extirpated—use mangrove estuaries as nesting habitat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…However, findings here strongly suggest that this is not the case-that hawksbills in this population do not immediately settle into the mangrove estuary, but instead spend at least a few years in an offshore, if not oceanic, habitat during their post-hatchling juvenile stage. These results are also supported by the SIA of hawksbill scute layers by Wedemeyer-Strombel et al (2021) which also found higher δ 13 C values in the earliest scute layers. This offshore movement pattern is further supported when the growth rates estimated in the current study are related to the length-frequency distribution of turtles found in both the mangrove estuary and the rocky reef habitats.…”
Section: Habitat Use and Movement Patternssupporting
confidence: 72%
See 4 more Smart Citations
“…However, findings here strongly suggest that this is not the case-that hawksbills in this population do not immediately settle into the mangrove estuary, but instead spend at least a few years in an offshore, if not oceanic, habitat during their post-hatchling juvenile stage. These results are also supported by the SIA of hawksbill scute layers by Wedemeyer-Strombel et al (2021) which also found higher δ 13 C values in the earliest scute layers. This offshore movement pattern is further supported when the growth rates estimated in the current study are related to the length-frequency distribution of turtles found in both the mangrove estuary and the rocky reef habitats.…”
Section: Habitat Use and Movement Patternssupporting
confidence: 72%
“…To isotopically distinguish two separate habitats, we referenced hawksbill skin stable isotope values previously published and from the current study to help characterize the mangrove estuary (Bahía de Jiquilisco, Wedemeyer-Strombel et al, 2021) and the rocky reef / ocean (Punta Amapala, current study) as two isotopically distinct locations (inside or outside estuary). In Wedemeyer-Strombel et al (2021), skin from juvenile (<65 cm CCL) hawksbills captured in Bahía de Jiquilisco had stable carbon isotope values that ranged from ca.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
See 3 more Smart Citations